A prospective study of the 6 min walk test as a surrogate marker for haemodynamics in two independent cohorts of treatment-naïve systemic sclerosis-associated pulmonary arterial hypertension. Issue 8 (31st August 2015) - Sanges, Sébastien; Launay, David; Rhee, Rennie L; Sitbon, Olivier; Hachulla, Éric; Mouthon, Luc; Guillevin, Loïc; Rottat, Laurence; Montani, David; De Groote, Pascal; Cottin, Vincent; Magro, Pascal; et al.
Abstract : Objectives: Despite the wide use of the 6 min walk distance (6MWD), no study has ever assessed its validity as a surrogate marker for haemodynamics and predictor of outcome in isolated pulmonary arterial hypertension associated with systemic sclerosis (SSc-PAH). We designed this work to address this issue. Methods: Treatment-naïve patients with SSc-PAH were prospectively included from two sources: the French PAH Network (a prospective epidemiological cohort) (n=83) and randomised clinical trials submitted for drug approval (Food and Drug Administration) (n=332). Correlations between absolute values of the 6MWD and haemodynamics at baseline, as well as between variations of 6MWD and haemodynamics during follow-up, were studied in both populations. Results: In the French cohort, baseline cardiac output (CO) (R 2 =0.19, p=0.001) and New York Heart Association class (R 2 =0.10, p<0.001) were significantly and independently correlated with baseline 6MWD in multivariate analysis. A significant, independent, but weaker, correlation with CO was also found in the Food and Drug Administration sample (R 2 =0.04, p<0.001). During follow-up, there was no association between the changes in 6MWD and haemodynamic parameters in patients under PAH-specific treatments. Conclusions: In SSc-PAH, CO independently correlates with 6MWD at baseline, but accounts for a small amount of the variance of 6MWD in both study samples. This suggests that other non-haemodynamic factors could have an impact on the walk distance. Moreover, variations of 6MWD do not reflect changes in haemodynamics among treated patients. Our results suggest that 6MWD is not an accurate surrogate marker for haemodynamic severity, nor an appropriate outcome measure to assess changes in haemodynamics during follow-up in treated SSc-PAH.